Intensive voice treatment (LSVT®) for patients with Parkinson's disease: a 2 year follow up - Ramig, L (BMJ Group, 2001)
OBJECTIVES—To assess long term (24 months) effects of the Lee Silverman voice treatment (LSVT®), a method designed to improve vocal function in patients with Parkinson's disease. METHODS—Thirty three patients with idiopathic Parkinson's disease were stratified and randomly assigned to two treatment groups. One group received the LSVT®, which emphasises high phonatory-respiratory effort. The other group received respiratory therapy (RET), which emphasises high respiratory effort alone. Patients in both treatment groups sustained vowel phonation, read a passage, and produced a monologue under identical conditions before, immediately after, and 24 months after speech treatment. Change in vocal function was measured by means of acoustic analyses of voice loudness (measured as sound pressure level, or SPL) and inflection in voice fundamental frequency (measured in terms of semitone standard deviation, or STSD). RESULTS—The LSVT® was significantly more effective than the RET in improving (increasing) SPL and STSD immediately post-treatment and maintaining those improvements at 2 year follow up.  CONCLUSIONS—The findings provide evidence for the efficacy of the LSVT® as well as the long term maintenance of these effects in the treatment of voice and speech disorders in patients with idiopathic Parkinson's disease.